THREE MAIN APPROACHES OF DIASPORA DIPLOMACY IN FOREIGN POLICY - A. A. Torrealba (Russian Journal of Economics and Law)
Objective: to analyze the notion of “diaspora diplomacy” and the main concepts connected with it.Methods: dialectic approach to cognition of the social phenomena, allowing to analyze them in their historical development and functioning in the context of the integrity of objective and subjective factors, which determined the choice of the following research methods: systemic-structural, formal-juridical, comparative.Results: it is proved in the article, that a diaspora is a part of a nation or a community located in different parts of the world outside the country of origin. In some states diasporas may develop strong ties with the leaders of their present countries, thus influencing their internal and external policy. This phenomenon is known in Americal science as “diaspora diplomacy”. In the recent period it has become increasingly important to analyze the objective and subjective factors of forming the external policy of some countries and the role of diaspora in this process. However, basing on the analyzed sources, we can conclude that the notion “Diaspora diplomacy” is still being formed, as it is being interpreted as various political realities. The studied scientific literature contains several approaches towards the notion of “Diaspora diplomacy”: a) a branch of political sociology of international relations; b) the basic tool for determining various types of external policy, c) diplomatic strategy. Scientific novelty: the article analyzes the notion of "Diaspora diplomacy", as well as the related basic concepts; describes the features of development dynamics of foreign relations between different countries and the role of diaspora in them. Practical significance: the main provisions and conclusions of the article can be used in research and teaching when addressing the issues of the nature of diaspora diplomacy and related concepts.